The IMPLEMENTATION OF BEHAVIOR CHANGE TECHNIQUES TO IMPROVE THE SELF-EFFICACY OF NEGLECTED CHILDREN IN CHILD SOCIAL PROTECTION SERVICE UNITS (SATPEL PSA) BANDUNG CITY - Septyan Berliana Sumaki; Meiti Subardhini; Sinta Yulianti Suyono (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
IMPLEMENTATION OF BEHAVIOR CHANGE TECHNIQUES TO IMPROVE THE SELF-EFFICIENCY OF NEGLECTED CHILDREN IN CHILD SOCIAL PROTECTION SERVICE UNITS (SATPEL PSA) BANDUNG CITY 1Septyan Berliana Sumaki Politeknik Kesejahteraan Sosial Bandung, Ir. H. Juanda No. 367, Dago, Bandung septiyan.berliana@gmail.com 2Meiti Subardhini Politeknik Kesejahteraan Sosial Bandung, Ir. H. Juanda No. 367, Dago, Bandung meiti.subardhini@gmail.com 3Sinta Yulianti Suyono Politeknik Kesejahteraan Sosial Bandung, Ir. H. Juanda No. 367, Dago, Bandung sintasuy@gmail.com Abstract This research refers to the application of behavior change techniques in various agreed specific behaviors so that they can have an influence on the level of self-efficacy. This study aims to describe the application of behavior change techniques in 3 aspects of self-efficacy, namely aspects of level, generality and strength. This research is a study with a Single Subject Design approach with quantitative methods. The respondents of this study were neglected children who received services at SATPEL PSA. The instruments used to measure baseline A1, treatment (B1) and baseline A2 were determined based on the results of the behavioral assessment that had been carried out, so that 6 behaviors were obtained with 18 specific behaviors. The application of behavior change techniques aims to reduce the child's maladaptive behavior, 6 behavior change techniques used are positive reinforcement, systematic desensitization, implosion, advice and instruction, motivation and behavioral contracts. The results of this study indicate that one neglected child who received services with the initials NF had self-efficacy in the moderate category with the measurement results from the three aspects 1203, where the level aspect had a value of 404 the generality aspect had a value of 392 and the strength aspect had a value of 407 all three were included in the category currently. The proposed program is “TERTUJU (Encouraged Behave For Advancement)” by providing services for the application of behavior change techniques to increase self-efficacy using the Social Casework method. Keywords: Behavior Modification Techniques; Self Efficacy; Homeless Child.